Semi-Empirical Modeling of the Atmospheres of the M Dwarf Exoplanet Hosts GJ 832 and GJ 581 - Tilipman, Dennis (2021)
Stellar ultraviolet (UV) radiation drives photochemistry, and extreme-ultraviolet (EUV) radiation drives mass loss in exoplanet atmospheres. However, the UV flux is partly unobservable due to interstellar absorption, particularly in the EUV range (100-912 Å). It is therefore necessary to reconstruct the unobservable spectra in order to characterize the radiation environment of exoplanets. In the present work, we use a radiative transfer code SSRPM to build one-dimensional semiempirical models of two M dwarf exoplanet hosts, GJ 832 and GJ 581, and synthesize their spectra. SSRPM is equipped with an extensive atomic and molecular database and full-NLTE capabilities. We use observations in the visible, ultraviolet, and X-ray ranges to constrain atmospheric structures of the modeled stars. The synthesized integrated EUV fluxes are found to be in good agreement with other reconstruction techniques, but the spectral energy distributions disagree significantly across the EUV range. More than two-thirds of the EUV flux is formed above 105 K. We find that the far-ultraviolet (FUV) continuum contributes 42%-54% of the entire FUV flux between 1450 and 1700 Å. The comparison of stellar structures of GJ 832 and GJ 581 suggests that GJ 832 is a more magnetically active star, which is corroborated by other activity indicators.